(untitled) (Swiss Medical Weekly, 2017)
Trafficking and sale of narcotics frequently involves the intra-abdominal transport of large quantities of drugs, usually cocaine or heroin (“body packing”), or, when there is a risk of being arrested, the oral ingestion of minor quantities of narcotics dedicated for immediate resale (“body stuffing”). This study aimed to describe the characteristics, complications and medical follow through of 132 cases of body packing (n = 36), cases of body stuffing (n = 83) or mixed cases (n = 13), referred by the authorities to our emergency department over the course of 12 years. Analysis of these 132 cases did not reveal any intra-abdominal rupture or leak of the packaging, or any case of acute intoxication. Nevertheless, a surgical intervention was required in three of the body packers (2.3%) owing to stasis of the packages inside the stomach. The mean length of stay was longer when the packets were located in the stomach at time of diagnosis than when they were lower in the gastrointestinal tract (61.9 vs 43.8 hours, respectively), but this was not statistically significant (p = 0.13). Length of stay was not associated with the presence of (nonspecific) symptoms or the total number of packs ingested. In conclusion, the study of this cohort of 132 body packers and body stuffers permits us to state that the medical management of these patients is rarely associated with serious complications, and that their length of stay is generally long, averaging 2 days before complete elimination of the drug packages.